The effectiveness of whole body cryotherapy compared to cold water immersion: Implications for sport and exercise recovery - Holmes, M.; Willoughby, D. S. (International Journal of Kinesiology & Sports Science, 2016)
Cryotherapy is the process of cooling the body, is typically used therapeutically, and is often used as a method of recovery relative to sport and exercise performance. The purpose of this review is to compare the current literature on WBC to that of CWI and determine whether WBC provides any additional enhancements for sport and exercise recovery. These include tissue temperature reduction, markers of muscle damage, markers of inflammation, and parasympathetic reactivation. Method: Common methods of cryotherapy include cold water immersion (CWI), ice packs, ice massages, and gel or cooling creams. CWI is the most common method among athletes; however, a new form of cryotherapy, known as whole-body cryotherapy (WBC), has recently emerged. Since its introduction, WBC has grown in popularity among practitioners and athletes. WBC involves short exposures (generally between 2-4 minutes) to very cold air (-100o C to -140o C) in a controlled room and setting. Furthermore, many of the studies on WBC were observational and did not contain a control group. Conclusion: Despite its growing popularity, the alleged benefits of WBC are largely based on anecdotal evidence as randomized, clinically-controlled studies regarding its efficacy are limited.